2018
DOI: 10.1016/j.jaad.2017.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Serration pattern analysis for differentiating epidermolysis bullosa acquisita from other pemphigoid diseases

Abstract: DIF serration pattern analysis is not restricted by variation in laboratory procedures, transport medium, or experience of observers. This learnable technique can be implemented as a routine diagnostic method as an extension of DIF microscopy for subtyping PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 17 publications
1
56
1
4
Order By: Relevance
“…At present, the diagnosis of anti-lam-c1 pemphigoid is based on a mix of clinical, histopathological and immune serological findings. 32 Although the significance of lam-c1-specific IgG autoantibodies is still unresolved, as ex vivo and in vivo models failed to show pathogenic properties of these autoantibodies, 24,25 their detection in the patients' sera is a diagnostic hallmark in establishing diagnosis of anti-lam-c1 pemphigoid. Previously, detection of IgG serum autoantibodies against a 200 kDa protein of dermal extracts was the standard immune serological procedure which is highly reliable but only available in a few specialized centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the diagnosis of anti-lam-c1 pemphigoid is based on a mix of clinical, histopathological and immune serological findings. 32 Although the significance of lam-c1-specific IgG autoantibodies is still unresolved, as ex vivo and in vivo models failed to show pathogenic properties of these autoantibodies, 24,25 their detection in the patients' sera is a diagnostic hallmark in establishing diagnosis of anti-lam-c1 pemphigoid. Previously, detection of IgG serum autoantibodies against a 200 kDa protein of dermal extracts was the standard immune serological procedure which is highly reliable but only available in a few specialized centres.…”
Section: Discussionmentioning
confidence: 99%
“…Zillikens et al 34 developed an assay based on IIF knockout analysis which allowed exclusion of EBA and anti-lam332-type mucous membrane pemphigoid. Lastly, Meijer et al 12,32 analyzed the serrated pattern profile of perilesional skin of anti-lam-c1 pemphigoid patients, and found that, in contrast to the u-serrated pattern for EBA sera, anti-lam-c1 pemphigoid presented with a n-serrated pattern, characteristic of BP. The lack of easily reproducible techniques strongly limits the diagnosis of antilam-c1 pemphigoid and leads to an under-recognition of this pemphigoid variant.…”
Section: Discussionmentioning
confidence: 99%
“…The “u‐serrated” pattern has arches closed at the bottom and an appearance like “growing grass”; this is pathognomonic for binding of antibodies against type VII collagen in epidermolysis bullosa acquisita and the rare cases of bullous systemic lupus erythematosus. The “n‐serrated” pattern has arches closed at the top, and is found in all other pemphigoid diseases (Figure ) . Recent studies showed that pattern diagnosis is easy to learn (an online training program is available at https://www.nversusu.umcg.nl ), has high inter‐observer conformity, and can be performed using 4 μm or 6 μm sections and a magnification of 400‐fold .…”
Section: Direct Immunofluorescence Microscopymentioning
confidence: 99%
“…Skin‐bound autoantibodies can be confirmed by fluorescent overlay antigen mapping, direct immunoelectron microscopy, and serration pattern analysis by DIF. Serration pattern analysis is an undervalued and learnable technique, and has proven additive value in differentiating EBA from other pemphigoid diseases, especially in seronegative patients, which represent approximately half of all patients with EBA . By close examination of the linear immunodeposition pattern along the BMZ, two distinct serrated patterns may be revealed: an n‐serrated pattern or a u‐serrated pattern (Fig.…”
Section: Epidermolysis Bullosa Acquisitamentioning
confidence: 99%